Learning Problems in the Implementation of the Independent Curriculum in State Junior High Schools - Murni, Deti; Kusen; Sumarto (Academicus: Journal of Teaching and Learning, 2024)
This research explores the evolution of the education curriculum in Indonesia, which often changes with changes in ministers, and explains its impact on the quality of learning, especially during the COVID-19 pandemic which forced a transition to an online system. The purpose of this research of knowing and describing Learning Problems in the Independent Curriculum that occurred at SMPN 2 Seberang Musi Kepahiang. This research departs from the background of the many phenomena surrounding learning problems in the Independent curriculum and various policies regarding the Independent curriculum. The research question raised is how learning problems in the Independent curriculum at SMPN 2 Seberang Musi Kepahiang are problematic. The research was conducted with a qualitative type of field research. Data was collected by interviewing school principals, curriculum representatives, and teacher councils as well as making observations SMPN 2 Seberang Musi Kepahiang. The results of these interviews were analyzed and then presented in a descriptive form. The results of this analysis can answer the questions formulated in the research questions. The results of this analysis are in the form of learning problems in the Independent curriculum originating from the government in the form of less than optimal guidance and assistance in the implementation of the Independent curriculum. In addition, there are also problems originating from teachers in the form of a lack of teacher ability to utilize Independent teaching platforms and utilize technology to learn and understand Independent curriculum.